A "Human Rights" of our own? Chinese and Turkish Encounters with a Western Concept. (November 2017) - Üngör, Çağdaş
This article aims to compare the Turkish and Chinese reception of the "human rights" term, which enjoyed wide currency across the globe after the end of the Cold War. During the 1990s, as the global human rights discourse was embraced by dissidents in Turkey and China, the state elites remained skeptical of this concept, which was often perceived as a tool of Western imperialism. Unlike nationalists, Muslim and Confucianist conservatives saw some merit in the term "human rights" and discussed ways to appropriate it in their local contexts. In China and Turkey, "human rights" was often instrumental in promoting collective identities during the 1990s. Although the term's original emphasis on the individual somewhat disappeared in these countries, its embrace by various groups demonstrates that "human rights" discourse resonates with non-Western audiences.